Quadriceps muscle activity during walking with a knee ankle foot orthosis is associated with improved gait ability in acute hemiplegic stroke patients with severe gait disturbance - Hayashi, Yusuke; Yamazaki, Kota; Komatsu, Shinya; Yamamoto, Naoaki; Ueda, Shujiro; Sato, Kazunori; Yamaguchi, Tomofumi; Hatori, Kozo; Honaga, Kaoru; Takakura, Tomokazu; Wada, Futoshi; Tanuma, Akira; et al. (Frontiers in Neurology, 2024)
A knee-ankle-foot orthosis (KAFO) prevents knee buckling during walking and enables gait training for acute hemiplegic stroke patients with severe gait disturbances. Although the goal of gait training with a KAFO is to improve gait ability, that is, to acquire walking with an anklefoot orthosis (AFO), it is not clear how gait training with a KAFO contributes to improving gait ability. Therefore, this study aimed to investigate the relationship between muscle activities during walking with a KAFO and the improvement of gait ability in hemiplegic stroke patients with severe gait disturbance.Methods: A prospective cohort study was conducted. Fifty acute hemiplegic stroke patients who could not walk with an AFO participated. Muscle activities of the paretic rectus femoris, biceps femoris, tibialis anterior, and soleus were assessed with surface electromyogram during walking with a KAFO. Electromyograms were assessed at the beginning of gait training and at the time the Ambulation Independence Measure score improved by 3 or higher, or discharge.Even in patients with complete hemiplegia, paretic rectus femoris, biceps femoris and soleus showed periodic muscle activity during walking with a KAFO. Twenty-three patients improved to an Ambulation Independence Measure score of 3 or higher and were able to walk with an AFO (good recovery group). At the beginning of gait training, paretic rectus femoris muscle activity during the first double-limb support phase was significantly higher in the good recovery group than in the poor recovery group. The rectus femoris muscle activity significantly increased from before to after acute rehabilitation, which consisted mainly of gait training with a KAFO. Discussion: For acute hemiplegic stroke patients with severe disturbance, the induction and enhancement of paretic quadriceps muscle activity during walking with a KAFO play an important role in acquiring walking with an AFO.